Origine du drainage rocheux acide dans la région d'Eagle Plains, Territoire du Yukon (Canada) et son impact sur les épinettes noires (Picea mariana (Mill)) - Doucet, Annick (University of Ottawa (Canada), 2007)
The construction of the Dempster Highway, a 736 km long gravel road located in the northern Yukon Territory, is believed to have initiated acid rock drainage nearby Eagle Plains. In this study, the spatio-temporal potential of dendrogeochemistry to understand the impacts of acidity on black spruce is testes and geochemical methods are used to examine the origin of acid rock drainage. The dendrogeochemical results suggest that the construction of the Dempster Highway in the 1970's did not initiate acid rock drainage near Eagle Plains, since elevated concentrations of trace and heavy metals were recorded in the 1940's, comparatively to the control site. However, in the acidified zone, there is an increase in trace metals in the 1970's, suggesting that the construction of the road amplified the release of acidity by exposing fresh pyrite-rich shale to the surface. The acidified stream, which originates from the excavated area, has a pH value averaging 3.1 +/- 0.3 and a solute concentration several orders of magnitude greater than the surface water collected from the adjacent control site. Active layer soluble ions are also characterized by a similar geochemical trend, although their concentration is slightly less. The plot of solute concentrations of the acidified stream and active layer soluble ions versus sulfates give similar slopes, suggesting a recycling of solutes, it is proposed that, after acid rock drainage was initiated, the effect of seasonal freeze-thaw of the active layer played an important rote in maintaining and recycling the acidity in the stream. During the freeze-back of the active layer, Fe sulfate minerals would precipitate, thus producing a large amount of H + that would be stored in the active layer. During the thaw season, this acidity would be released, thus enhancing further dissolution of clays and alumino-silicate minerals. The release of these contaminants by acid rock drainage, not only causes a perturbation of the water quality, but has a negative impact on the sensitive nearby Arctic ecosystem. The vegetation surrounding the acidified stream shows important signs of deterioration, a higher rate of mortality and zones without vegetation. This absence of vegetation has an impact on the depth of seasonal thaw by increasing the depth by twice compared to the adjacent control site.
Keywords: Physical Geography.; Geochemistry.